Charge ordering and structural distortions at low temperature in La2-2xSr1+2xMn2O7 (x=0.475 and 0.5) - Wilkins, S; Spencer, P; Beale, T; Hatton, P; von Zimmermann, M; Brown, S; Prabhakaran, D; Boothroyd, A (2003)
In this paper we present x-ray scattering results of charge and orbital ordering in the bilayer manganite La2-2xSr1+2xMn2O7 with doping levels x = 0.5 and x = 0.475. Using high-energy x-ray scattering, the structural modulation due to the Jahn-Teller ordering and the charge ordering due to the Mn3+/Mn4+ pattern have been measured. Both the x = 0.5 and x = 0.475 samples are found to display charge and Jahn-Teller order. We have confirmed that the wave vectors of the Jahn-Teiler order, charge order, and orbital order are Q→ = (0.25,0.25,0), Q→ = (0.5,0.5,0) and Q→ = (0.25,0.25,0). The origin of these has been confirmed by resonant x-ray scattering in the vicinity of the Mn K edge using polarization analysis. Contrary to previous studies, the Jahn-Teller order is found to be not reentrant, but is found to reduce in intensity at temperatures below 140 K for both samples. Charge ordering was also detected in the x = 0.5 sample below this temperature.